2014
DOI: 10.1017/jmo.2014.25
|View full text |Cite
|
Sign up to set email alerts
|

Different strokes: IPO risk factors, investor valuation, and firm survival

Abstract: Link to this article: http://journals.cambridge.org/abstract_S183336721400025X How to cite this article: Fariss-terry Mousa, Paul E. Bierly, III and William J Wales (2014). Different strokes: IPO risk factors, investor valuation, and rm survival. AbstractAs a firm prepares for initial public offering, the Securities and Exchange Commission mandates that top managers must record risks to their firms' survival or performance in the prospectus. More specifically we propose that external risk factors (market risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 78 publications
(154 reference statements)
0
3
0
Order By: Relevance
“…Ahmad and Jelic [16] have investigated the impact of lock-up provisions on the IPO survival of the firms listed on the London stock exchange. Mousa et al [49] have studied the impact of risk factors and investor valuation on the survival of US high-tech firms. Ayadi et al [1] have examined the survival of reorganized French firms using conventional determinants of IPO survival.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Ahmad and Jelic [16] have investigated the impact of lock-up provisions on the IPO survival of the firms listed on the London stock exchange. Mousa et al [49] have studied the impact of risk factors and investor valuation on the survival of US high-tech firms. Ayadi et al [1] have examined the survival of reorganized French firms using conventional determinants of IPO survival.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…The above findings show the impact of risk disclosures on IPO underpricing. The results of the previous studies are not conclusive because one section of previous studies (Wasiuzzamn et al, 2018;Hussein et al, 2019;McGuinness, 2019;Gaulin, 2017) found the positive impact of risk disclosures on IPO underpricing, whereas the other one (Falconieri and Tastan, 2018;Ding, 2016;Mousa et al, 2014;Campbell et al, 2014) found the negative impact of risk disclosures on IPO performance. This means no clear evidence has been found in the previous studies done over the period of time across various contexts.…”
Section: Resultsmentioning
confidence: 93%
“…Despite its prominence, idiosyncratic risk doesn't predict future returns, rendering firms with higher idiosyncratic risk less appealing to investors with limited stock holdings. Moreover, external and internal risk factors, including market, legal, and operational risks, as well as management and technical risks, influence investor sentiment and the long-term survival of IPO firms (Mousa et al, 2014). Both external and internal risk factors positively correlate with the probability of firm failure, impacting investor confidence.…”
Section: Idiosyncratic Riskmentioning
confidence: 99%